Towards exposure limits for working postures and musculoskeletal symptoms – a prospective cohort study. Issue 9 (1st September 2016) - Coenen, Pieter; Douwes, Marjolein; van den Heuvel, Swenneke; Bosch, Tim
Abstract: Occupational postures are considered to be an important group of risk factors for musculoskeletal pain. However, the exposure-outcome association is not clear yet. Therefore, we aimed to determine the exposure-outcome association of working postures and musculoskeletal symptoms. Also, we aimed to establish exposure limits for working postures. In a prospective cohort study among 789 workers, intensity, frequency and duration of postures were assessed at baseline using observations. Musculoskeletal pain was assessed cross-sectionally and longitudinally and associations of postures and pain were addressed using logistic regression analyses. Cut-off points were estimated based on ROC-curve analyses. Associations were found for kneeling/crouching and low-back pain, neck flexion and rotation and neck pain, trunk flexion and low-back pain, and arm elevation and neck and shoulder pain. The results provide insight into exposure-outcome relations between working postures and musculoskeletal symptoms as well as evidence-based working posture exposure limits that can be used in future guidelines and risk assessment tools. Practitioner Summary: Our study gives insight into exposure-outcome associations of working postures and musculoskeletal symptoms (kneeling/crouching and low-back pain, neck flexion/rotation and neck pain, trunk flexion and low-back pain, and arm elevation and neck and shoulder pain). Results furthermore deliver evidence-based postural exposure limits that can be used in guidelines and risk assessments.